The problem of self-consciousness of the French and Russian soldiers era of the Napoleonic wars (in their memoirs) - V. S. Kalmykov (Vestnik MGIMO-Universiteta)
From the era of the Napoleonic wars separate us for 200 years, but with each anniversary year the interest in this time and events. The brightest page of that time was undoubtedly the Patriotic War of 1812. About the battle and the war written numerous books and articles, but most interesting are the memoirs of direct participants in the events, which include the armed forces of the Russian and French armies. They allow you to see the era of the Napoleonic Wars through the eyes of those directly involved, to understand their attitude to the war and the enemy, to determine their understanding of their duty.